AN ANALYSIS STUDENTS’ PROBLEM IN ENGLISH SPEAKING AT THE SECOND GRADE OF SMAN 1 POMALAA - La Ode Muh Idrus Hamid; Rais Abin; Meisi Meisi (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2022)
One of the most difficult language skills to master is speaking. This also applied to SMAN 1 Pomalaa. The English teacher of the school stated that the speaking skills of the second-grade students" of the school is fairly bad. They are not able to answer simple questions in English. This was the reason the researcher wanted to find out the problems that were faced by students in speaking English at the second-grade of SMAN 1 Pomalaa. The design of this research was descriptive qualitative. The subjects were 20 students of the second-grade class. The researcher gathered data by distributing questionnaires and then interviewing the students to answer the research questions. The findings of the research showed that the students had problems in two categories, namely linguistic and psychological. The former consisted of the lack of vocabulary mastery (2.9), poor grammar mastery (2.9), and poor pronunciation (2.9). Meanwhile, the latter consisted of the lack of self-confidence (3.2) and anxiety (2.9). Furthermore, the most dominant problem is the lack of self-confidence and anxiety.